Caracterização estrutural e funcional de um inibidor de PLA2 presente no plasma da cascavel sulamericana (Crotalus durissus terrificus) - Roberta Marcia Marques dos Santos (2005)
Crotoxi (Ctx) is the main toxic component of the venom of Crotalus durissus terrificus, the South American rattlesnake. Ctx is a heterodimer of CB, a neurotoxic phospholipase A2 (PLA2) and CA, which is devoid of any enzymatic or neurotoxic activity. The blood plasma of C. d. terrificus contains an endogenous inhibitor, named CNF for Crotalus neutralizing factor that is able to inhibit both lethal and enzymatic activities of the homologous venom. The biological action of CNF is due to the replacement of CA in Ctx complex (CACB) and formation of a new stablecomplex CNFCB. In the present work, a novel methodology for purification of active CNF from the crude snake plasma was developed. CNF in nature exists as a mixture of a glycosylated and a deglycosylated forms and the carbohydrate moiety was shown to be unnecessary for its inhibitory activity. The interference of CNF on the binding of radio iodinated Ctx, composed of CA and a single isoform of (CB CA-125ICB2), to rat brain synaptosomes was evaluated under different conditions. Competition by unlabeled Ctx and CA was run in parallel. CNF was able to inhibit the binding of Ctx to synaptosomes under all condition tested, including displacing the toxin already bound to its membrane target. A model of interaction between Ctx, target receptor and CNF, previously proposed, was updated. The linear peptide segments probably involved in the interaction between the proteins in the complexesof CA or CNF with two main isoforms of CB (CB1 and CB2) were mapped by spot multiple peptide syntesis. These segments were identified in a three-dimensional model proposed for the CB isoforms as possible linear interaction sites.